PEDULI COVID-19” PRODUKSI HAND SANITIZER, MASKER DAN PEMBERIAN BANTUAN SEMBAKO UNTUK MASYARAKAT GARUT YANG TERIMBAS KORONA VIRUS - Diah Wardani; Nurul; Gina Nafsa Mutmainna; Mamay; N. Ai Erlinawati; Hasbi Taobah Ramdani; Desy Syswianti; Andhika Lungguh Perceka (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
The increasing cases of Covid-19 in Indonesia have a sizable health impact on the community. The growth of the Covid-19 virus sticks to hands every day through physical contact with the environment, and among other things it can cause/cause various diseases. For this reason, these microorganisms need to be destroyed or prevented from spreading. One of the easiest and most appropriate ways is to wash your hands with soap and clean running water. Preventive efforts are needed to deal with it, bearing in mind that this outbreak cannot be considered an ordinary pandemic. In order to anticipate wider spread, the Lecturer Team for the D3 Pharmacy Study Program and D3 Health Analyst and in collaboration with LP4M STIKes Karsa Husada Garut made hand sanitizers which will be distributed to residents around Jayaraga, Tarogong Kidul, Garut. Hand sanitizer is a prevention effort by washing hands and soap, if there is no water and soap you can use a hand sanitizer. Some time ago, the supply of hand sanitizers was very limited, so to help the community as well as self-use, they made their own hand sanitizers. Staple food is one of the main and most important things which as a form of concern for STIKes Karsa Husada Garut is always present in the community. Moreover, assistance in the form of groceries is able to ease the burden on the community, especially in the midst of a sluggish economy due to the corona virus.